The Implementation of Games in Vocabulary Learning at the English Education Department FBS UNIMA - Samola, Nurmin (English Education Department, 2023)
The foundation of English is vocabulary which must be acquired Reading listening writing and speaking are all made easier with a strong vocabulary The purpose of this study was to determine whether or not the usage of language games can enhance students learning achievement in acquiring English vocabulary given that mastering English vocabulary is essential and important The outcomes of this research are anticipated to improve vocabulary knowledge Since this study relies on data and statistics it adopts a quantitative methodology The authors use the pre experimental approach in their investigation There are two tests: the initial test which is administered prior to therapy and the final test which is administered following treatment According to the study s findings the post test score score of 7 is greater than the pre test score 4 8 This proves that games are a highly effective way to improve kids interest in vocabulary Since learning becomes interactive and can pique students imaginations it can be concluded that the learning model that incorporates educational games will increase student interest in learning Additionally instructional games will give pupils a fresh way to learn< p>